Andrew Manson and Bernard Mbenga, Land, Chiefs, Mining: South Africa’s North West Province since 1840 (Historia, 2021)
Interest in the historical dynamics of ethnicity and land owndership in South Africa have been on the rise recently. In the introduction to this work, the authors deal with the importance of the history of the Setswana-speaking population of today's North West Province of South Africa. They also provide detail on the location of the province and show that the territory offers a number of unique features, including its important mining industry. The authors have in the past published scholarly work on the Batswana and their history. In this publication, they continue in the same vein by highlighting some of the neglected aspects of Batswana history.
Keywords: book reviews; setswana; North West; mining